Povezanost kvalitete života i psihološkog aspekta bolesnika s acne vulgaris - Kotrulja, Lena (Array, 2003)
Acne vulgaris is a common inflammatory dermatosis capable of producing psychological and physical scarring. It is common for patient to develop psychological problem as a consequence of the condition, such as those related to low self-esteem, social phobias, depression, anxiety, suicidal thoughts, and lowered quality of life. Self assessment of acne severity is often more severe than dermatological clinical evaluation what is important data in understanding the necessity of individual approachement to the patient. Isotretinoin is the drug which is indicated in treatment of severe form of the disease, but in last period its application is suggested in moderate form of acne with prominent cicatricial liability or when the disease has strong psychological impact on patients life. Last 15 years some data of possible association with depression and suicidal tendency during treatment with isotretinoin appeared. We have started a prospective clinical trial using standardised psychometriq questionnaire (APSEA, DSQL, BDI, STAI, MPS) and psychological interview which included patient with acne vulgaris who started with isotretinoin treatment in two Dermatological Clinics in Croatia (Zagreb and Osijek). The results will be helpful in the final definition of criteria for the use of isotretinoin in the treatment of acne vulgaris and the influence of isotretinoin therapy on psychological status of patient.